Causal relationship between coherent self-awareness and basic psychological needs with psychological well-being: considering the mediating role of mind-awareness in students. - Abedin, Tayebeh; Ghodsi, Parvaneh; Taghiloo, Sadegh; Davaei, Mehdi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: appropriate educational facilities, along with the active and motivated minds of learners, will lead to the progress of the country; Therefore, one of the important research priorities in this field is to identify and investigate the effective factors in the mental health of students, which are considered the main components of the educational system. Therefore, the present study was conducted with the aim of investigating the causal relationship between coherent self-awareness and basic psychological needs with psychological well-being with regard to the mediating role of mindfulness in middle school students of Tehran. Method: This descriptive correlational study was conducted on a sample of 352 people, who were selected by multi-stage cluster sampling method from among all secondary school students of the 2nd district of Tehran in the academic year of 2019-1400. Ghorbani et al.'s (2008), basic psychological needs of LaGuardia et al.'s (2000), Rief's psychological well-being (1989) and Freiburg's mindfulness (2006) questionnaires were implemented and the data were collected using descriptive statistics, Pearson correlation and structural equation modeling methods in P>0.01 significance level was analyzed by AMOS software and SPSS version 24. Results: The structural model of predicting psychological well-being based on basic psychological needs and self-knowledge, with the mediation of mindfulness in students, had an acceptable and favorable fit (P